Bolstering clinician resilience through an interprofessional, web-based nightly debriefing program for emergency departments during the COVID-19 pandemic. Issue 5 (2nd September 2020) - Azizoddin, Desiree R.; Vella Gray, Kristen; Dundin, Andrew; Szyld, Demian
ABSTRACT: The COVID-19 pandemic has instigated significant changes for health care systems. With clinician burnout rising, efforts to promote clinician resilience are essential. Within this quality improvement project, an interprofessional debriefing program (Brigham Resilience in COVID-19-pandemic Emergency Forum-BRIEF) was developed within two emergency departments (EDs). An interprofessional group of ED providers led optional, nightly debriefings using a web-based portal to connect with ED clinicians for six weeks. In total, 81 interprofessional staff participated in nightly debriefings with a 47% attendance rate. On average, three participants attended the BRIEF nightly (range = 2–8) to discuss the challenges of social distancing, scarce resources, high acuity, clinician burnout and mental health. Participation increased as rates of COVID-19 positive patients rose. Debriefing leaders provided ED leadership with summaries of clinician experiences and suggestions for improvements. Feedback supported quality improvement initiatives within the ED and greater mental health support for staff. Clinicians and administrators provided positive feedback regarding the program's impact on clinician morale, and clinical processes that promoted the safety and quality of patient care. Optional debriefing with receptive departmental leadership may be a successful tool to support clinicians and hospitals during critical events.